Robustness Report: "Going to a Better School: Effects and Behavioral Responses", by Cristian Pop-Eleches and Miguel Urquiola (2013) - Douglas Campbell; Abel Brodeur; Magnus Johannesson; Joseph Kopecky; Lester Lusher; Nikita Tsoy (Institute for Replication (I4R), 2024)
Pop-Eleches and Urquiola (2013) apply a regression discontinuity to the Romanian secondary school system, and notably find that (a) students who go to a better school get higher scores on an exam used for university admission, (b) parents of students who get into a better school help their kids less with homework, and (c) kids who go to a slightly better school report more negative interactions with peers. We first reproduce all regression tables in Pop-Eleches and Urquiola (2013), and then test for robustness by unstacking the data, multi-way clustering, altering the cutoffs, altering control variables, and conducting influential analysis. Overall, we find the results for finding (a), (b), and (c) are robust in 100%, 42%, and 60% of the robustness checks we ran, and the t/z scores were on average 93%, 69%, and 92% as large as the original study.
Keywords: I21; I28; J13; 330; Education; Peer Effects; Economics of Education